Improving thermal conductivity through welding boron nitride nanosheets onto silver nanowires via silver nanoparticles. (16th June 2019) - Fu, Chenjie; Yan, Changzeng; Ren, Linlin; Zeng, Xiaoliang; Du, Guoping; Sun, Rong; Xu, Jianbin; Wong, Ching-Ping
Abstract: Enhancing the thermal conductivity of polymers is important for their critical applications in all heat exchangers and electronic packaging. However, owing to the existence of interfacial thermal resistance (ITR), the overall thermal conductivity of the polymer composites cannot meet the requirements of the electronics industry. Here, we propose an approach to decreasing the ITR by both improving the contact area and the interconnection between fillers. An increase in out-of-plane thermal conductivity (0.804 W m −1  K −1 ) is observed in the silver nanoparticles (AgNPs)-boron nitride nanosheet (BNNS)/silver nanowires (Ag NW)/epoxy composites, which is 2.4 times higher than that of the BNNS/epoxy composites. Fitting the measured thermal conductivity of composites with Foygel model indicates that ITR can be reduced effectively when the contact and the interactions of the fillers is optimized. The proposed design methodology here potentially paves the way for designing and preparing higher thermal conductive materials in the future.